Interval Versus Continuous Single-leg Training on Capillarization and the Satellite Cell Response - Padilla, Reinnier (My University, 2019)
Skeletal muscle satellite cells (SC) are essential in muscle repair and regeneration. The role of SCs in mediating hypertrophic adaptations following resistance training has been widely studied. Recent evidence from endurance training studies suggest that SCs may also play a role in mediating non-hypertrophic adaptations. Indeed, it has been shown that satellite cells respond to endurance training. Work in rodent models suggest that exercise intensity may play an important role in expanding the SC pool whereas the results of endurance training studies in humans are much less consistent. Limited evidence also suggest that exercise intensity may be important in mediating exercised-induced capillarization following endurance training in humans. In both instances, it is unknown whether the on-and-off pattern characteristic of interval training (i.e. the rest-work cycles) plays a role in the magnitude of these skeletal muscle responses to this type of exercise. Thus, we sought to determine if the rest-to-work cycle plays a role in the scope of these skeletal muscle responses by comparing the SC response and capillarization to two distinct work-matched protocols that are performed at the same intensity but at two different exercise patterns (interval versus continuous). We hypothesized that interval exercise will elicit a greater SC response and induce greater capillary growth compared to work-matched continuous exercise. Ten young active individuals performed 12 sessions of counterweighted single-leg cycling over 4 weeks. Each leg was randomly assigned to Interval (INT) (10 x 3-min intervals at 50% of single leg peak power output (PPO), with 1 min recovery) or Continuous (CONTIN) (30 min at 50% PPO, followed by 10 min recovery), which were performed 5 min apart on each day, in an alternating order. Resting muscle biopsies were obtained from the vastus lateralis pre- and post-training. Immunofluorescent microscopy of muscle cross sections was used to assess muscle fibre capillarization, SC expansion and activation. Western blot analysis was performed on pro-angiogenic factors, specifically VEGF and VEGFR2. Mixed muscle SC activation increased in the INT leg compared to the pre-training time-point (3.2 ± 0.5 vs. 1.5 ± 0.2 Pax7+/MyoD+ cells/ 100 myofibers, respectively; P < 0.05). Mixed muscle SC activation did not increase significantly in the CONTIN leg compared to the pre-training time-point and there was no significant difference in activation between CONTIN and INT post-training. With regards to capillarization, no differences in type I or type II muscle fibre CC (capillary contacts), C/Fi (individual capillary-to-fibre ratio) or CFPE (capillary-to-fibre perimeter exchange index) were observed post-training or between legs. No significant expansion of the SC pool occurred in either legs post-training and no increases in fibre cross-sectional area was observed. This study presents novel evidence of mixed muscle SC activation following interval exercise training that is not observed following work- and intensity-matched continuous exercise training. This suggest that the rest-to-work cycle associated with interval exercise may dictate, to some extent, SC activation whereas it may not be a primary stimulus for training-induced changes in capillarization.
Keywords: exercise physiology; satellite cells; capillarization; interval training